Medicago truncatula copper transporter 1 (MtCOPT1) delivers copper for symbiotic nitrogen fixation. Issue 2 (19th January 2018) - Senovilla, Marta; Castro‐Rodríguez, Rosario; Abreu, Isidro; Escudero, Viviana; Kryvoruchko, Igor; Udvardi, Michael K.; Imperial, Juan; González‐Guerrero, Manuel
Summary: Copper is an essential nutrient for symbiotic nitrogen fixation. This element is delivered by the host plant to the nodule, where membrane copper (Cu) transporter would introduce it into the cell to synthesize cupro‐proteins. COPT family members in the model legume Medicago truncatula were identified and their expression determined. Yeast complementation assays, confocal microscopy and phenotypical characterization of a Tnt1 insertional mutant line were carried out in the nodule‐specific M. truncatula COPT family member. Medicago truncatula genome encodes eight COPT transporters. MtCOPT1 ( Medtr4g019870 ) is the only nodule‐specific COPT gene. It is located in the plasma membrane of the differentiation, interzone and early fixation zones. Loss of MtCOPT1 function results in a Cu‐mitigated reduction of biomass production when the plant obtains its nitrogen exclusively from symbiotic nitrogen fixation. Mutation of MtCOPT1 results in diminished nitrogenase activity in nodules, likely an indirect effect from the loss of a Cu‐dependent function, such as cytochrome oxidase activity in copt1‐1 bacteroids. These data are consistent with a model in which MtCOPT1 transports Cu from the apoplast into nodule cells to provide Cu for essential metabolic processes associated with symbiotic nitrogen fixation.